Symbolism and meaning of solar heart amulets - Sousa, Rogério (2012)
We present in this study a brief description of the main morphological and symbolic features of the solar heart amulet. Under this designation we consider the heart amulets that present a sun disk over the top of the object. Starting with a morphological description of these artefacts, we will also consider in this article the study of the artistic rendering of this particular type of heart amulets as a way to clarify its symbolism.